Case report: Recurrent hemobilia due to hepatic artery pseudoaneurysm mimicking gastrointestinal tract bleeding - Wang, Jiaoyang; Yang, Lei; Xu, Lijun; Qin, Lijie; Cheng, Yanwei (Frontiers in Medicine, 2023)
Hemobilia, a rare form of upper gastrointestinal bleeding (UGIB), is a potentially fatal complication that usually occurs after iatrogenic hepatobiliary trauma. However, hemobilia is clinically challenging to diagnose and often gets too late to diagnose. We herein report a case of recurrent hemobilia due to hepatic artery pseudoaneurysm (HAP) that was initially misdiagnosed as gastrointestinal tract bleeding. However, the patient was treated successfully with percutaneous coil occlusion of the pseudoaneurysm. This case illustrates that hemobilia can present as a mimic of gastrointestinal tract bleeding, but this is often difficult to diagnose at first glance and often misleads clinicians, especially emergency physicians, into making an incorrect diagnosis. Familiarity with the clinical features of hemobilia can help raise clinical suspicion and facilitate the early diagnosis and treatment of hemobilia.